265 Supermarket Health Advocacy, Resources, and Education (SHARE): Results of a pilot community-based diabetes screening and education program - Renee Cadzow; Andrew Strohmeier; Marchelle Brooks; Chelsea Okocha; Dennis Lee (Journal of Clinical and Translational Science)
Objectives/Goals: To screen community members for prediabetes and diabetes in the grocery stores located in urban areas, identify gaps in healthcare access, promote healthy food, teach participants about diabetes prevention and management, and learn from them via interactive community-based educational sessions. Methods/Study Population: 303 Tops Friendly Market customers in urban Buffalo, NY participated in this program. Customers without a diabetes diagnosis took a CDC Prediabetes Risk Test (score >5  =  prediabetes risk). Those with a previous diabetes diagnosis took a survey about their diabetes knowledge/management, healthcare access, and social determinants of health. Participants received a $5 voucher for fruit and vegetables. We conducted 5 educational sessions using an adult learning, participatory education approach. A $10 gift card was given for attendance. Participants shared questions/concerns and strategies to overcome barriers. We answered questions and collected information on barriers to diabetes care. Results/Anticipated Results: Seven-six participants (25%) had a diabetes diagnosis. Of these, 91% saw a doctor every 3 months, but 28% did not know the importance of HbA1c. 18% had trouble paying for medications, 15% had inadequate transportation. 227 took the Prediabetes Risk Test: 58% had a score >5, 47% had diabetes family history, 51% had hypertension, and 75% had a BMI that put them at risk for diabetes. 86% of those with a score5. 55 people (34 unique) participated in 5 sessions. We actively listened to diabetes perceptions, concerns, successes and barriers/facilitators to self-management, and discussed diabetes management strategies for heathier eating and lifestyle. Discussion/Significance of Impact: It is feasible to screen for health conditions in the supermarket setting, which can be an equalizer in enhancing access to healthcare. This study helped identify gaps in care and provided education. Importantly, people receiving this intervention lived in the poorest neighborhoods in Buffalo.